How do athletes cause ball flight path deviation in high-performance interceptive ball sports? A systematic review - Lindsay, C.; Clark, B.; Middleton, K.; Crowther, R.; Spratford, W. (International Journal of Sports Science & Coaching, 2022)
Athletes alter ball flight trajectory in interceptive ball sports to change task constraints that their opponents must overcome to successfully meet the ball in flight. This systematic review identified how athletes change their techniques to alter the ball flight trajectory in high-performance interceptive sports where the ball is projected by the hand towards an opponent. Studies that reported the kinematics or ball flight characteristics of these movements were searched for using SportsDiscus, Scopus, MEDLINE and CINAHL Plus databases up to 27 April 2021. Forty-eight articles met the inclusion criteria, including 19 baseball, 12 cricket, five handball, four softball, three volleyball and five water polo studies. Extracted data were presented as ranges and descriptively analysed to report athlete sporting actions. Trajectory deviation can be caused by imparting an altered seam orientation or spin rate and axis of rotation on the ball. Athletes impart sidespin or manipulate seam orientation to cause lateral deviation while topspin and backspin are used to create vertical changes in the flight path. Adjusting the shoulder, forearm, wrist, hand and fingers of the throwing or striking arm can be used to impart an altered seam orientation or spin rate and axis of rotation on the ball. The findings of this review could assist coaches and athletes across a variety of sports to improve the ability to deviate the ball during flight.